Profitabilitas, Likuiditas dan Pertumbuhan Perusahaan pada Kebijakan Hutang Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2018 – 2022 - Mira Santika (Universitas 45 Surabaya, 2024)
This research aims to determine and analyze the influence of profitability, liquidity and company growth on the debt policy of manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This type of research is quantitative research using secondary data obtained from the Indonesia Stock Exchange website. The total population is 226 companies and the sample is 25 companies with a total of 125 observations. Sampling used purposive sampling technique. The data analysis method uses Ordinary Least Square, with a panel data regression model approach and statistical t-test.The research results show that: Profitability/ROA has a negative and insignificant effect on the debt policy of manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. Liquidity/CR has a positive and significant effect on the debt policy of manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. Company growth / GROWTH has a positive and significant effect on the debt policy of manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period.